IMPLEMENTASI KEBIJAKAN PENGEMBANGAN PARIWISATA BERBASIS AGROWISATA DI KECAMATAN MODOINDING KABUPATEN MINAHASA SELATAN - EKEL, AGNES FIRANTI (Sam Ratulangi University, 2020)
The purpose of this research is to know how to implement the policy of Agrowisata-based tourism developmentin Modoinding Sub-district of South Minahasa Regency.This research uses qualitative research methods. The data collection techniques used in this study are:interview, documentation, observation. The informant in this study is all implementing organizations(Governments) and communities as a service recipient. To achieve the information, other informant from thepublic are selected through snowball sampling technique.The results of the research obtained the fact that the horticultural farmers in the district Modoinding havedifficulty capital to develop their plantations because the help given by the government is very little so that notenough for the cost of the plantation is forced to borrow money from the bank through the Business CreditProgram (KUR) for that they ask the Government's commitment to be able to distribute assistance to thefarmers so that Horticultural farmers in the district Modoinding also hopes to the local government to carryout training activities to the farmers about the way of planting good and modern crops to the quality of plantsespecially vegetable-can be increased and achieve a better standard such as Modoinding potato that is wellknownquality.Keywords: policy implementation, tourism development, agrotourism